SUPERVISI AKADEMIK BERKELANJUTAN DALAM MENINGKATKAN KOMPETENSI GURU PADA PENYUSUNAN SILABUS DAN RPP - Iis Jenab (IKIP Siliwangi Bandung, 2019)
Abstrak: Preparation of learning tools such as silabus and plans for implementing learning by teachers at SDN Cibabat mandiri 4 has not been maximized. Therefore, in this study, research was carried out with an ongoing academic supervision title in improving teacher competencies in compiling learning devices. The purpose of this study was to improve the understanding of teachers in SDN Cibabat mandiri 4 in making learning devices. The method used in this study is the method of school action research with observation instruments. The results of his research are that there is an increase in the ability of SDN Cibabat mandiri 4 teachers in compiling learning devices.